Title: Understanding a Low Vitamin D State in the Context of COVID-19 - Walsh, James Bernard; McCartney, Daniel M.; Laird, Éamon; McCarroll, Kevin; Byrne, Declan G.; Healy, Martin; O’Shea, Paula M.; Kenny, Rose Anne; Faul, John L. (Frontiers in Pharmacology, 2022)
While a low vitamin D state has been associated with an increased risk of infection by SARS-CoV-2 in addition to an increased severity of COVID-19 disease, a causal role is not yet established. Here, we review the evidence relating to i) vitamin D and its role in SARS-CoV-2 infection and COVID-19 disease ii) the vitamin D status in the Irish adult population iii) the use of supplemental vitamin D to treat a deficient status and iv) the application of the Bradford-Hill causation criteria. We conclude that reverse causality probably makes a minimal contribution to the presence of low vitamin D states in the setting of COVID-19. Applying the Bradford-Hill criteria, however, the collective literature supports a causal association between low vitamin D status, SARS-CoV-2 infection, and severe COVID-19 (respiratory failure, requirement for ventilation and mortality). A biologically plausible rationale exists for these findings, given vitamin D’s role in immune regulation. The thresholds which define low, deficient, and replete vitamin D states vary according to the disease studied, underscoring the complexities for determining the goals for supplementation. All are currently unknown in the setting of COVID-19. The design of vitamin D randomised controlled trials is notoriously problematic and these trials commonly fail for a number of behavioural and methodological reasons. In Ireland, as in most other countries, low vitamin D status is common in older adults, adults in institutions, and with obesity, dark skin, low UVB exposure, diabetes and low socio-economic status. Physiological vitamin D levels for optimal immune function are considerably higher than those that can be achieved from food and sunlight exposure alone in Ireland. A window exists in which a significant number of adults could benefit from vitamin D supplementation, not least because of recent data demonstrating an association between vitamin D status and COVID-19. During the COVID pandemic, we believe that supplementation with 20-25ug (800–1000 IU)/day or more may be required for adults with apparently normal immune systems to improve immunity against SARS-CoV-2. We expect that higher monitored doses of 37.5–50 ug (1,500–2,000)/day may be needed for vulnerable groups (e.g., those with obesity, darker skin, diabetes mellitus and older adults). Such doses are within the safe daily intakes cited by international advisory agencies.